PENGARUH PERENCANAAN ANGGARAN DAN LINGKUNGAN BIROKRASI TERHADAP PENYERAPAN ANGGARAN PADA SKPD DI KOTA BANDA ACEH - Ifra Zachrand 'Athaya (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study examines the influence of budget planning and bureaucratic environment on budget absorption in Regional Work Units of Banda Aceh City. Budget absorption is a key indicator of the effectiveness and success of public sector programs and activities. The research employs a quantitative approach using multiple linear regression analysis to test the relationship between budget planning, bureaucratic environment, and budget absorption. Data collection was carried out using structured questionnaires distributed to Regional Work Units officials directly involved in financial management processes. The findings demonstrate that both budget planning and bureaucratic environment have significant and positive effects on budget absorption, both partially and simultaneously. Effective budget planning ensures the timeliness and precision of program implementation, while a supportive bureaucratic environment facilitates better coordination and minimizes administrative delays. This study provides critical insights for local governments to enhance the efficiency of budget management and improve public service delivery, ultimately contributing to better public welfare.